2018
DOI: 10.1111/jfb.13821
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific morphological and reproductive trait variation in mouth almighty Glossamia aprion (Apogonidae) across different flow environments

Abstract: Intraspecific variability, although comparably less studied than interspecific variation, is an important tool in understanding population responses to environmental gradients. This study investigated intraspecific trait variation across three contrasting aquatic flow habitat types (intermittent creek, billabong and river) in a common mouth‐brooding freshwater fish in northern Australia, the mouth almighty Glossamia aprion. Samples of G. aprion were collected at various sites, within the Daly River catchment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
(128 reference statements)
0
4
0
Order By: Relevance
“…Mouthbrooding in fishes is likely to be a particularly costly parental care investment for the caring parent, where the ability of brooders to ingest food and conduct normal gill function is likely to be af- (Jakob et al, 1996;Le Cren, 1951) can be influenced by season, reproductive state (spawning), morphological factors and the availability of resources in the environment (Abecia et al, 2018;Beesley et al, 2021;Luiz et al, 2019). In our study, brooders of both species showed a general reduction in at least one body condition index relative to nonbrooders.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Mouthbrooding in fishes is likely to be a particularly costly parental care investment for the caring parent, where the ability of brooders to ingest food and conduct normal gill function is likely to be af- (Jakob et al, 1996;Le Cren, 1951) can be influenced by season, reproductive state (spawning), morphological factors and the availability of resources in the environment (Abecia et al, 2018;Beesley et al, 2021;Luiz et al, 2019). In our study, brooders of both species showed a general reduction in at least one body condition index relative to nonbrooders.…”
Section: Discussionmentioning
confidence: 49%
“…The diversion of body energy resources from tissue maintenance to caring for young is an important potential reproductive cost to the adult care giver (Alonso‐Velando & Alvarez, 2012). Variations in relative body condition (often used a proxy measure of body fitness in fishes (Jakob et al, 1996; Le Cren, 1951) can be influenced by season, reproductive state (spawning), morphological factors and the availability of resources in the environment (Abecia et al, 2018; Beesley et al, 2021; Luiz et al, 2019). In our study, brooders of both species showed a general reduction in at least one body condition index relative to nonbrooders.…”
Section: Discussionmentioning
confidence: 99%
“…This species is a paternal mouthbrooder, where males incubate eggs and larvae in their buccal cavity for 2–3 weeks (Fauth, 2017; Pusey et al ., 2004). G. aprion is reported to show sexual dichromatism during the breeding period (Fauth, 2017; Pusey et al ., 2004) and exhibit intraspecific variation in morphological traits as a response to habitat variability and predominant flow conditions (Abecia et al ., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…We investigate patterns of paternity in broods of two freshwater paternal mouthbrooders from divergent fish families, mouth almighty Glossamia aprion (Apogonidae) and blue catfish Neoarius graeffei. Although these species are fairly poorly studied, G. aprion spawns all year round, incubates for two to three weeks and has a fecundity of 104-532 and brood size of 4-416 eggs [16][17][18][19][20][21], Contrastingly, N. graeffei spawns during the wet season only, incubates for four to five weeks and has a fecundity of 4-128 and brood size of 1-88 eggs [17,18,21]. For both species, mouthbrooding comes at the expense of the parent's feeding, body condition and digestive and respiratory capacities [17].…”
Section: Introductionmentioning
confidence: 99%